2016
DOI: 10.1038/mi.2015.145
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct genital tract HIV-specific antibody profiles associated with tenofovir gel

Abstract: The impact of topical antiretrovirals for pre-exposure prophylaxis on humoral responses following HIV infection is unknown. Using a binding antibody multiplex assay, we investigated HIV-specific IgG and IgA responses to envelope glycoproteins, p24 Gag and p66 in the genital tract and plasma following HIV acquisition in women assigned to tenofovir gel (n=24) and placebo gel (n=24) in the CAPRISA 004 microbicide trial to assess if this topical antiretroviral had an impact on mucosal and systemic antibody respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 67 publications
3
17
0
Order By: Relevance
“…The first approach examined six different antibody effector functions with two cell types: Natural Killer Cells and Monocytes across four different vaccine studies. Confirming earlier reports, the analysis by LASSO (the least absolute shrinkage and selection operator) and PLSDA (partial least‐squares discriminant analysis) also identified that HIV‐1 envelope IgG3 uniquely distinguished the efficacious vaccine RV144 regimen from the non‐efficacious VAX003 vaccine regimen. In a correlation network analysis using non‐case– control samples, the antibody effector functions of antibody‐dependent cellular cytotoxicity (ADCC), antibody‐dependent cell‐mediated phagocytosis (ADCP), and antibody‐dependent complement deposition (ADCD) were tethered to Env IgG1 and IgG3 responses.…”
Section: Immunological Mechanisms Of Protectionsupporting
confidence: 80%
“…The first approach examined six different antibody effector functions with two cell types: Natural Killer Cells and Monocytes across four different vaccine studies. Confirming earlier reports, the analysis by LASSO (the least absolute shrinkage and selection operator) and PLSDA (partial least‐squares discriminant analysis) also identified that HIV‐1 envelope IgG3 uniquely distinguished the efficacious vaccine RV144 regimen from the non‐efficacious VAX003 vaccine regimen. In a correlation network analysis using non‐case– control samples, the antibody effector functions of antibody‐dependent cellular cytotoxicity (ADCC), antibody‐dependent cell‐mediated phagocytosis (ADCP), and antibody‐dependent complement deposition (ADCD) were tethered to Env IgG1 and IgG3 responses.…”
Section: Immunological Mechanisms Of Protectionsupporting
confidence: 80%
“…Similar to our findings, a recent study using samples from the CAPRISA 004 microbicide trial to determine if topical antiretroviral usage had an impact on mucosal and systemic antibody responses found that HIV-specific IgA and IgG responses are increased in the genital tract of individuals who acquire HIV infection in the presence of tenofovir gel (27). Since all women were HIV-1 seronegative at the time of sample collection, our findings suggest that a local IgA-mediated immune response to HIV-1 may be elicited through sexual HIV-1 exposure without resulting in a systemic anti-HIV-1 IgG response.…”
Section: Discussionsupporting
confidence: 76%
“…Binding of mucosal antibodies to HIV-1 Env proteins were measured by a custom HIV-1 binding antibody multiplex assay as described [3,4,[60][61][62][63]. Env proteins used included gp41, gp120 (clade B BaL), gp140 (consensus M ConS), V1/V2 loop (clade B CaseA V1/V2), and resurfaced core (RSC) proteins revealing the CD4bs (RSC3, and mutants RSC3Δ371, RSC3G367R, RSC3Δ371P363N abolishing CD4bs antibody binding [64]).…”
Section: Hiv-1-specific Binding Antibody Assaymentioning
confidence: 99%